Ribosome pausing, a dangerous necessity for co-translational events. Issue 3 (6th September 2019) - Collart, Martine A; Weiss, Benjamin
Abstract: In recent years translation elongation has emerged as an important contributor to the regulation of gene expression. There are multiple quality control checkpoints along the way of producing mature proteins and targeting them to the right cellular compartment, or associating them correctly with their partners. Ribosomes pause to allow co-translational protein folding, protein targeting or protein interactions, and the pausing is dictated by a combination of the mRNA sequence and structure, the tRNA availability and the nascent peptide. However, ribosome pausing can also lead to ribosome collisions and co-translational degradation of both mRNA and nascent chain. Understanding how the translating ribosome tunes the different maturation steps that nascent proteins must undergo, what the timing of these maturation events is, and how degradation can be avoided when pausing is needed, is now possible by the emergence of methods to follow ribosome dynamics in vivo . This review summarizes some of the recent studies that have advanced our knowledge about co-translational events using the power of ribosome profiling, and some of the questions that have emerged from these studies.